Thematic Search in National Libraries Catalogs: Experience of Baltic States - Halytska, Svitlana (Bìblìotečnij vìsnik, 2020)
Solving the problem of quality management of electronic catalog requires the creation of new approaches to the formation of catalog databases, clear interaction of all its components, instructional and methodological support of all work processes of scientific processing of documents, as well as the quality and completeness of bibliographic records. The article deals with the means of thematic search by library classification in the electronic catalogs of the national libraries of the Baltic countries.The purpose of the articleis to highlight the experience of the national libraries of the Baltic States in the use of bibliographic records of documents as search tools, powerful means of electronic communication.Presentation of the main material. Libraries of the Baltic States use in library technology the Universal Decimal Classification translated into thenational language and subject headings that take into account national characteristics. The bibliographic records of documents indicate the adopted classification decisions: classification indices and subject headings, which are active elements of information retrieval languages.The possibilities of different information and library search systems are compared. It has been found that it is important to include classification indexes and subject sections inthe bibliographic records of documents, which enables the user to limit the search to a specific topic area. Conclusions.It is noted that bibliographicrecords of documents are able to provide a full thematic search and connection between electronic catalog databases, to become a powerful means of electronic communication only if the records contain certain elements of linguistic support of library technology. The use of classifications, subject headings and thesauri during scientific processing of documents, parallel indexing by different classifications, indication of classification indexes and topics in the bibliographic record of the document, use of classification solutions as search elements - all this is a reliable basis for high level of modern information requests. capabilities of their information retrieval systems, development in terms of electronic communication. A necessary element of modern interlibrary communication is also the mandatory introduction into the system of thematic search of a national library ofan international classification system, such as UDC.